Optical shape analysis based on discrete Fourier transform and second-order moment analysis of the brightness distribution for the detection of sub-micron range tracks in nuclear emulsion - Umemoto, Atsuhiro; Naka, Tatsuhiro; Nakano, Toshiyuki; Kobayashi, Ryuta; Shiraishi, Takuya; Asada, Takashi (Progress of theoretical and experimental physics, 2020)
Abstract To recognize sub-micron-range low-energy tracks recorded in a super-fine-grained nuclear emulsion (Nano Imaging Tracker), an elliptical fitting method was devised to analyze anisotropic images taken by an optical microscope. We report on this newly developed method using a discrete Fourier transform and second-order moment analysis of the brightness distribution. We succeeded in lowering the ellipticity threshold, thereby improving the selection efficiency and angular resolution. Notably, the success of detecting carbon 30 keV tracks is the first such achievement in the world, where the incident direction of carbon 30 keV ions was determined with an accuracy of 41$^°$ and an efficiency of $1.7 ± 0.1%$.